Utilization of Internet Services among Students of Polytechnic Institutions in Kwara State - Adebayo, Alimi Emmanuel; Ochayi, Onojah Amos (Indonesian Journal of Multidiciplinary Research, 2022)
Internet services had made the entire world a global village. But the utilization of Internet services have been jeopardized by major problems and one of the problems is security which is one of the greatest threat. This study investigated the utilization of internet services among students of the polytechnic institutions in Kwara state. The descriptive method of the survey type was used to gather accurate information on the assessment of the utilization of the Internet among students. The findings established that chat, entertainment, and social networking are the most disturbing activities associated with the utilization of Internet services. Also, few students showed the problem of sleeplessness at night and decline in academic performance due to internet usage and there was a significant difference between male and female utilization of Internet services. The study concluded that it can be concluded that social activities were seen as the most activities students carry out on the internet. It was thus recommended that students should be encouraged in their usage of Internet services to boost their academic performance in school and for social networking purposes.